2017
DOI: 10.13164/re.2017.0064
|View full text |Cite
|
Sign up to set email alerts
|

A Compact Dual Band-Notched Circular Ring Printed Monopole Antenna for Super wideband Applications

Abstract: In this article, a simple and compact dual bandnotched (DBN) super wideband (SWB) printed monopole antenna (PMA) has been proposed. The proposed antenna composed of a circular PMA, which is connected through a 50-Ω triangular tapered microstrip fed line (TTMFL) and a round-cornered finite ground plane (RCFGP). It exhibits a very wide frequency band from 1.6-25 GHz (ratio bandwidth of 15.63:1) with a voltage standing wave ratio (VSWR)  2. By employing a U-shaped parasitic element (USPE) near the RCFGP and a T-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 17 publications
0
30
0
Order By: Relevance
“…The optimized antenna dimensions are given in Table I. It is observed that the dimensions of the antenna are reduced by 30% compared to those with same geometry reported in literature [10], [12].This antenna has a ratio bandwidth (RB) of 11.04. The current densities of the antenna at different frequencies of SWB are shown in the Fig.…”
Section: Antenna Simulation and Analysismentioning
confidence: 86%
See 1 more Smart Citation
“…The optimized antenna dimensions are given in Table I. It is observed that the dimensions of the antenna are reduced by 30% compared to those with same geometry reported in literature [10], [12].This antenna has a ratio bandwidth (RB) of 11.04. The current densities of the antenna at different frequencies of SWB are shown in the Fig.…”
Section: Antenna Simulation and Analysismentioning
confidence: 86%
“…On the same type of substrate, a tapered microstrip fed circular ring radiating patch with round cornered ground plane has been implemented in [9] to obtain a lower bound frequency of 1.6 GHz. A SWB antenna on FR4 substrate have been reported in [10] with an offset fed egg shaped patch having fractal ground plane and in [11] with a microstrip fed clover shaped radiating patch. Using the same substrate and co-planar waveguide (CPW) feed, a partially egg shaped slot antenna [12] and a fractal radiating patch antenna [13] has also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some antennas have been reported in which dual band notch functions are incorporated . Two stub resonators are used to produce each notch characteristics . Dual notched band characteristics is achieved by using π‐shaped slot and EBG resonator .…”
Section: Introductionmentioning
confidence: 99%
“…Specifically speaking, CP is generated when two orthogonal electric filed vectors are excited simultaneously. In the literature, different techniques have been proposed to excite these orthogonal vectors and stimulate CP feature [1][2][3][4][5]. Although contributing to significant improvements and applicable methods, there are still challenges in design of CP antennas regarding the CP purity, size reduction, and further performance enhancement.…”
Section: Introductionmentioning
confidence: 99%